Content Credibility in Short-Form Travel Videos and Travel Intention of Millennials and Young Consumers in Indonesia - Magsyanda Meliana; Putu Gde Arie Yudhistira (Department of Family and Consumer Sciences, Faculty of Social and Human Ecology, IPB University, 2026)
Background: Short-form travel videos on social media increasingly shape how millennials and young consumers form travel perceptions and intentions. However, limited research explains how credibility embedded in such content influences travel intention through psychological mechanisms. Purpose: This study examines the effect of content credibility in short-form travel videos on travel intention by incorporating emotional engagement and destination image as mediators, and social media engagement as a moderator. Methods: Drawing on the S–O–R framework, this study employed a quantitative cross-sectional design. A total of 421 Indonesian Gen Y and Gen Z social media users aged 18 and above were recruited through purposive online sampling. Eligible respondents were active social media users with prior exposure to short-form travel videos. Data were analyzed using PLS-SEM. Findings: This study found that content credibility, comprising content trustworthiness, informativeness, and visual appeal, has both direct and indirect positive effects on travel intention. In particular, emotional engagement and destination image have a mediating relationship on participants’ affective and cognitive pathways, respectively. Meanwhile, social media engagement strengthens selected relationships, meaning that more actively engaged users are more responsive to credibility cues. Conclusion: These findings confirm content credibility as a key predictor of travel intention, operating through complementary emotional and cognitive processes in short-form video contexts. Research implications: This study extends the S–O–R framework by conceptualizing credibility at the content level and integrating dual psychological pathways with a behavior-based moderating mechanism, offering deeper insights into digital tourism persuasion.